Studi Penempatan Sumur Resapan Berdasarkan Nilai Laju Infiltrasi, Kualitas Fisik Air, dan Tekstur Tanah pada DAS Air Timbalun dan Sungai Pisang Kota Padang - Fajar Inaqtiyo; Rusli HAR (Journals Mining Engineering : Bina Tambang, 2020)
Abstract. Groundwater is a vital natural resource for humans whose availability is diminishing due to population growth. Where the infiltration area located east of the city of Padang began to changes into housing, offices, etc. This causes a reduction in catchment areas, flooding and decreasing environmental quality, especially groundwater in the Air Timbalun and Sungai Pisang Watershed. To reduce flooding in the Air Timbalun and Sungai Pisang Watershed, a study of placement of infiltration wells was conducted based on infiltration rate values, physical quality of groundwater, and soil texture.The study was conducted at 26 points in the alluvium area of the Air Timbalun and Sungai Pisang watershed. With the data obtained of groundwater physical quality data, soil texture, and other supporting data.Based on the data obtained the average value of infiltration rate in the study area of 0.058828 cm/minute is classified as a low absorption area (<0.5 cm/minute). After conducting research by observant statistical analysis of linear regression, physical quality of water, soil texture, lithology conditions, and land use in the Air Timbalun and Sungai Pisang Watershed. So the placement of absorption wells is spread over 14 points in the Air Timbalun and Sungai Pisang Watershed, Padang City. Keywords: Absorption Wells, Infiltration Rate, Physical Quality of Groundwater, Soil Texture, Lithology